Social Perspective of Prevailing Sanitary practices among Urban Population - Rewathy, K. (Department of Sociology, Faculty of Arts, University of Colombo, 2021)
The condition of Sri Lanka is not in a safe hand for the pandemic. A lot of sanitation practices and safe methods are followed by the urban population compared to village community. Since the down town areas are seemingly crowded, people being extra vigilant towards their health and protection. Every stores and public gathering places in urban, strictly following the standard sanitary practices according to the government’s health guidelines. This study was conducted to get the public perspective towards the prevailing sanitary practices and their view point towards the continuation of the same. Therefore, 50 working individuals in different sectors were chosen for the questionnaire survey through purposeful convenience sampling method. Participants were chosen from different ages to gather various aspects of the particular matter. Accordance with the public recognition of the phenomenon, individual health care practices have been found. Common urban environmental issues were exposed by the participants and the sanitary practices such: wearing masks, washing hands often, using sanitizers, and having immunity boosting food. Youngsters and the mid aged community prefer the continuation of the sanitary practices even after the pandemic. But the elderly community refused to engage in such practices cause of the disability and inability. Advantageous of the continuation of sanitary practices in the urban were given by the urban population. Therefore, the public gathering places in the urban keep doing the sanitary practices in a prolonged manner, which could mitigate more health issues in the future. Though the study is limited to the urban area, this path could lead to further studies with different regions.
Keywords: Covid-19, Health, Urban, Sanitary, Population